Pemenuhan Aksesibilitas Bagi Penyandang Disabilitas - Syafi'ie, M (INKLUSI, 2014)
Accessibility is a very pivotal discourse for people with dissabilities as it encourages their equal participation and independence in the society. Accessibility, in this paper, is divided into 2 (two) kinds, which are physical and nonphysical one. The physical accessibility refers to accesibilty in the relations with buildings and environment whereas the nonphysical one corresponds to communication, information and technology. This paper also reveals testimony from various activists of DPOs (disabled people organizations). The data presented here was collected in 2012 through qualitative study in DIY (Yogyakarta Special Province). The paper concludes that eventhough Indonesia has been enacted regulations on accessibilty to people with disabilities, its implementation is ineffectice and discrimination still occurs to the population.